2018
DOI: 10.1136/bjophthalmol-2018-312199
|View full text |Cite
|
Sign up to set email alerts
|

Cycloplegic refraction by 1% cyclopentolate in young adults: is it the gold standard? The Anyang University Students Eye Study (AUSES) 

Abstract: A school-based study including 7971 undergraduates was conducted in Anyang, Henan Province, China. Cycloplegia was achieved with two drops of 1% cyclopentolate and 1 drop of Mydrin P (Tropicamide 0.5%, phenylephrine HCl 0.5%) with a 5 min interval. Non-cycloplegic and cycloplegic refractions were measured by an autorefractor. A paired-sample t-test and Spearman correlation analysis were used for analysis with data from only the right eyes included.  RESULTS: Of the 7971 students examined, 7793 (97.8%) with com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
38
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 23 publications
2
38
0
2
Order By: Relevance
“…32,35,40,41 Furthermore, in our previous study comparing the differences between cycloplegic and noncycloplegic refraction among these university students, a similar prevalence of 95.3% was found if myopia was defined by noncycloplegic refraction, while it decreased to 83.2% with myopia defined by cycloplegic refraction. 39 Thus, the prevalence of myopia and high myopia seems to be overestimated in their study. The prevalence of myopia in our study was higher than that reported in university students from Europe and the United States, [16][17][18][19][20][21][22] while consistent with prevalence reported in other studies in Asia, such as those in Taiwan, 23 and Singapore (Table 4).…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…32,35,40,41 Furthermore, in our previous study comparing the differences between cycloplegic and noncycloplegic refraction among these university students, a similar prevalence of 95.3% was found if myopia was defined by noncycloplegic refraction, while it decreased to 83.2% with myopia defined by cycloplegic refraction. 39 Thus, the prevalence of myopia and high myopia seems to be overestimated in their study. The prevalence of myopia in our study was higher than that reported in university students from Europe and the United States, [16][17][18][19][20][21][22] while consistent with prevalence reported in other studies in Asia, such as those in Taiwan, 23 and Singapore (Table 4).…”
Section: Discussionmentioning
confidence: 79%
“…32 Besides, cycloplegia by 1% cyclopentolate for those university students was also proved to be necessary in our previous paper, which reported a similar prevalence of myopia based on noncycloplegic refraction with theirs (95.3% vs. 95.5%). 39 Therefore, this is the first well-designed and large-scale study with comprehensive ophthalmologic examinations and cycloplegic data among university students in mainland China. In this paper, we report the prevalence of refractive errors, as well as the potential impact of demographic factors, with data on other ophthalmic diseases to be presented elsewhere.…”
mentioning
confidence: 97%
“…This evidence proved it a reliable screener for myopia. However, given the fact that the data from non-cycloplegic photoscreeners tend to over-estimate the prevalence of myopia [ 18 , 33 , 34 ], the actual prevalence may be lower than reported. This has been elaborated in our previous study that the SER results from Spot photoscreener overall represent a myopic shift, with an average of − 0.17D ~ − 0.49D [ 9 ].…”
Section: Photoscreening and Corrections For Photoscreener Resultsmentioning
confidence: 99%
“…It is important to note that refractive errors were measured without cycloplegia, which could overestimate the percentage of myopia 33. Myopia overestimation and hyperopia/emmetropia underestimation were observed previously when a cutoff of −0.5 D was used 33,34. However, the magnitude of overestimation is unknown when a cutoff of −0.75 D is used.…”
Section: Discussionmentioning
confidence: 96%
“…The high reported prevalence has been widely observed in East Asians, which could possibly be explained by the differences in environmental factors among East Asian children compared to Western children, in terms of less time spent outdoors as they are subjected to a more rigorous educational system 2532. It is important to note that refractive errors were measured without cycloplegia, which could overestimate the percentage of myopia 33. Myopia overestimation and hyperopia/emmetropia underestimation were observed previously when a cutoff of −0.5 D was used 33,34.…”
Section: Discussionmentioning
confidence: 99%